Mentransformasi Generasi Kepemimpinan Kristen Berlandaskan Teori Perkembangan Iman Karya James W. Fowler - Yunardi Kristian Zega; Hermina Sulistiawati; Otieli Harefa; Hendrik Bernadus Tetelepta (UKI Press, 2023)
Today there is a leadership crisis, especially in Christian institutions. For example, the process of selecting church leaders or synods cannot be separated from elements of Corruption, Collusion and Nepotism (KKN). This shows that Christian leadership is experiencing moral and faith degradation. Therefore, the purpose of this study is to provide an overview of transforming generations of Christian leaders who are in accordance with the teachings of the Bible, based on James W. Fowler's 6 stages of faith development theory. For this reason, this research uses descriptive qualitative research with a literature approach. The results obtained include: First, at the age of 0-6 years, growing children's confidence and self-confidence. Second, at the age of 6-12 years, set an example regarding the morals and integrity of leadership. Third, At the age of 12-18 years, take care of the children's association and environment. Fourth, at the age of 18-25 years, provide religious teachers who can become role models in leadership. Fifth, at the age of 25-40 years, form an open point of view. Sixth, At the age of 40 and above, adjust to the views of others and see the truth from many points of view. With this in mind, cases that often occur in the Christian leadership environment will be minimized.